Design of Smart Door Lock System Based on VLC and Fire Monitoring in Space (Case Study: Chemical Laboratory of SMAN 1 Pacet) - Wilana, Aprilia Orrin; Koesmarijianto, Koesmarijianto; Mas’udia, Putri Elfa (Politeknik Negeri Malang, 2024)
The school chemistry laboratory is a public facility for all members. So, good room security system is needed, considering the room stores hazardous chemicals are flammable. Therefore, a solution is offered to development door security system and fire monitoring in space. The purpose of this research to create and design VLC (Visible Light Communication) based door security system and to design a fire monitoring system in space. ESP32 is used as a microcontroller, temperature sensor (DS18B20), MQ-2, photodiode module, and IR Flame Infrared. The result of this research is that the maximum distance for sending passwords that can be received by the receiver is 30cm, lux <123, tilt angle 165°-180°. IR Flame Infrared can detect fire <11cm away, lux < 200. DS18B20 has sensor reading accuracy 99.97%, MQ-2 detects gas more than 300ppm. The IR Flame Infrared sensor reads the wavelength value according to the light source, namely Infrared Spectrometer. Dot have error tolerance 7ms, while dashes are 7.6ms. Overall, the system can run well. The door can be opened in two ways, using smartphone flash from outside and button from inside the room. In addition, the system can also detect fire at temperatures >50°C, wavelength <1100nm, and gases >300ppm